2017
DOI: 10.1186/s12933-017-0584-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of metformin with ascorbic acid versus acetyl salicylic acid on diabetes-related cardiovascular complication; a 12-month single blind multicenter randomized control trial

Abstract: BackgroundWe aimed to investigate the efficacy of ascorbic acid and acetylsalicylic acid among type II diabetes mellitus patients using metformin (only) for diabetes management therapy.MethodA 12-month single blinded multicenter randomized control trial was designed to investigate the measured variables [Glycated Hemoglobin (HbA1c), Renal function, Albumin Creatinine Ratio (ACR) etc.]. The trial was randomized into 2 experimental parallel arms (ascorbic acid vs acetylsalicylic acid) were blinded with study sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Interestingly, we did not find a significant improvement in HbA1c despite improvement in post‐prandial glucose responses. Previous studies that reported significant improvements in HbA1c after AA supplementation included more participants, enrolled participants with a higher baseline HbA1c and/or undertook AA supplementation for a longer period than we did. Nonetheless, other findings we report suggest that HbA1c may be improved with a more prolonged supplementation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we did not find a significant improvement in HbA1c despite improvement in post‐prandial glucose responses. Previous studies that reported significant improvements in HbA1c after AA supplementation included more participants, enrolled participants with a higher baseline HbA1c and/or undertook AA supplementation for a longer period than we did. Nonetheless, other findings we report suggest that HbA1c may be improved with a more prolonged supplementation period.…”
Section: Discussionmentioning
confidence: 99%
“…8 Improvements in insulin sensitivity with AA supplementation may subsequently promote improvements in glycaemic control. Indeed, findings of some studies, 7,[9][10][11][12] but not others, 13 support the efficacy of AA supplementation in improving glycaemic outcomes, including lowering of HbA1c and fasting glucose concentrations in individuals with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis of 15 randomized control trials (RCTs) investigating vitamin C supplementation and insulin resistance and biomarkers of glycaemic control (fasting glucose, HbA1c) found that doses of ≥200 mg/day vitamin C significantly reduced glucose concentrations in patients with T2DM, particularly if the intervention was for more than 30 days and in older individuals [ 36 ]. Furthermore, a recent 12 month RCT found that treating those with T2DM with both Metformin and vitamin C was more effective at reducing HbA1c and risk factors for diabetes-related long-term complications than treating with Metformin alone [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 10 Monitoring and control of blood glucose is a viable tool to determine disease control and rational therapy. 3 , 6 However, several studies reported a strong influence of patient-related factors on blood glucose intolerance, including perception and self-care behavior. 3 , 6 , 8 , 11 Self-care, including self-monitoring of blood glucose, showed a positive effect on controlled glycemic levels, 4 , 7 , 9 , 10 , 11 considering the fact that diabetes-related disease knowledge plays a vital role in association with self-care behaviors of a patient.…”
Section: Introductionmentioning
confidence: 99%
“… 15 None of the studies have discussed these factors among Malaysian populations. Malaysia is a multiethnic society with different lifestyle patterns and religious practices, 2 , 3 , 8 , 9 mainly consisting of Malay, Chinese, and Indian ethnicity. In this diverse population, it is essential to determine the HRQoL multiconstruct model.…”
Section: Introductionmentioning
confidence: 99%